Design and Development of an Android-Based Merchandise Management Application for K-pop Consignment Services - Nilam Putri Cahyani; Sutarman Sutarman (JISA (Jurnal Informatika dan Sains))
The rapid development of technology has increased various societal needs, especially in the e-commerce sector, including the delivery service of K-pop merchandise. The global popularity of K-pop has led to high demand for related merchandise such as albums, lightsticks, and exclusive clothing and accessories, often difficult to source internationally. This demand creates challenges for businesses in managing product data, inventory, and transactions effectively. Zena.id, as a business providing K-pop merchandise delivery services, faces specific issues with ensuring accurate transaction recording and real-time inventory monitoring. An efficient system is needed to reduce human error, prevent inventory discrepancies, and meet customer expectations for product availability. This research aims to develop an Android-based application to automate transaction recording and inventory monitoring at Zena.id. The application is designed to improve operational efficiency through an integrated system for accurate stock monitoring and transaction processing. Developed using the Kotlin programming language and an Agile approach, this method allows for flexible, iterative improvements. Testing results showed a 83.33% accuracy rate in transaction processing and inventory updates, significantly simplifying management tasks and reducing potential errors. Additionally, the user-friendly interface enhances satisfaction for both business managers and customers. This application serves as an optimal solution to address the unique challenges faced by K-pop merchandise delivery services in the digital era.